Analisis Penerapan PPh 23 Pada PT. Prima Indonesia Logistik - Oktania, Mila; Syafina, Laylan (Universitas Labuhanbatu, 2021)
This study aims to determine the suitability of income tax accounting article 23 for the services and leases of PT Prima Indonesia Logistik. This study used descriptive qualitative method. Data collection techniques are interviews and documents. The results of the study show that Article 23 Income Tax is the most important thing, the same as other taxes, so the company must do the calculation, deposit and self-report on the use of services from other parties and other income in connection with services. The service collector will issue withholding evidence as proof of withholding for services and receive withholding evidence from third parties on other income and the withholding receipt received will be used in the calculation of income tax as an advance.